Democratic humility : Reinhold Niebuhr, neuroscience, and America's political crisis - Beem, Christopher (Lexington Books, 2015)
Reinhold Niebuhr helps us to understand why our politics is broken and research on the brain confirms his analysis: we are all vain and self-righteous, and far too quick to reject anyone who thinks otherwise. To restore a democracy that works, we need to understand ourselves better and develop the humility such knowledge should engender.